Cardiac contractility modulation therapy improves health status in patients with heart failure with preserved ejection fraction: a pilot study (CCM‐HFpEF). (11th August 2022) - Linde, Cecilia; Grabowski, Marcin; Ponikowski, Piotr; Rao, Ishu; Stagg, Angela; Tschöpe, Carsten
Abstract: Aims: This pilot study aimed to assess the potential benefits of cardiac contractility modulation (CCM) in patients with heart failure with preserved ejection fraction (HFpEF). Methods and results: This was a prospective, multicentre, single‐arm, pilot study of CCM therapy in patients with HFpEF and New York Heart Association (NYHA) class II or III. Echocardiographic parameters were measured by an echo core laboratory to determine study eligibility. After CCM device implantation, patients were followed for 24 weeks. Overall, 47 patients (mean age 74.3 ± 4.4 years, 70.2% female) were enrolled, with left ventricular ejection fraction of 59 ± 4.4%, 63.8% with hypertension, 46.8% with atrial fibrillation, 40.4% with diabetes, 31.9% with at least one heart failure hospitalization in the prior year, 61.7% in NYHA class III, and Kansas City Cardiomyopathy Questionnaire (KCCQ) overall summary score of 48.9 ± 21.7. The primary efficacy endpoint (mean change in the KCCQ overall summary score) improved by 18.0 ± 16.6 points ( p  < 0.001) and there was an event‐free rate of 93.6% for the primary safety endpoint (device‐ and procedure‐related complications), as adjudicated by an independent physician committee. Conclusion: This pilot study demonstrates that the benefits of CCM may extend to the HFpEF patient population. The significant improvement in health status observed, with no obvious impact on safety, suggests that utilization of CCM for patients with HFpEF could prove to be promising. Abstract : The study primary endpoint – Kansas City Cardiomyopathy Questionnaire (KCCQ) overall summary score at baseline and 24‐week follow‐up and change from baseline. CCM, cardiac contractility modulation; HFpEF, heart failure with preserved ejection fraction; LVEF, left ventricular ejection fraction; CSS, clinical summary score; TSS, total symptom score.